Removal of Humic Substances from Aqueous Solutions Using Carbon Quantum Dots and Activated Carbon Derived by Watermelon Rind - Mohammad Pirbavepour; Bahareh Lorestani; Maryam Kiani Sadr; Mehrdad Cheraghi; Atefeh Chamani; Fatemeh Houshmand (Journal of Water and Environmental Nanotechnology)
Sustainable and green adsorbents for water and wastewater treatment have gained attention worldwide in the last decades. Water contaminated with humic substances (HSs) has become an emerging human health threat due to producing disinfection by-products (DBPs) which react with chlorine and result in carcinogenic materials such as THMs. This study was conducted to remove HSs from aqueous solutions using nano-scale biosorption based on watermelon rind (WR), as a cost-efficient adsorbent. The effects of factors such as time, adsorbent dosage, pH and concentration, and then reaction kinetics and isotherms on the adsorption process were investigated. FTIR, XRD, BET analysis SEM, and also TEM were used to evaluate the structural characteristics of the adsorbent. The characteristics showed that increasing the temperature of thermal oxidation and loading of NH4Cl on the adsorbent surface increases the porosity and surface area, leading to an increase in adsorption performance. Also, given effective factors that increase the time and dose of adsorbent and reduce the initial concentration, The removal efficiency of humic acid (HA) increased with the following conditions: time 45 min and pH=4 and the adsorbent equal to 0.1 gr/L at a concentration of 50 mg/L, the removal efficiency of HSs reached 93.89%. The experiments showed that the adsorption process showed a better match with the pseudo-quadratic synthetic model with a coefficient of determination R²=0.99, while the adsorption isotherm was consistent with the Langmuir adsorption model. Studies have shown that adsorption occurs in a single layer. The thermodynamic parameters show that the process is spontaneous.